City and city model: Villaviciosa as a territory-project in Central Asturias - Martínez Fernández, Luis Carlos; Olay Varillas, David (Street Art & Urban Creativity, 2025)
The municipality of Villaviciosa, due to improvements in infrastructure, has been defined in recent years by its progressive integration into the central urban region of Asturias, of which it forms its northeastern edge. However, better connectivity with this space that brings together population, activity and services, has generated tensions of various kinds derived from an increase in territorial competitiveness, fundamentally in terms of attracting and fixing population and economic activity. This scenario of constant evolution is an opportunity for growth, but also a threat which requires concrete actions and strategies with new creative approaches to territorial planning, capable of preserving the values of the municipality, while advancing comprehensive and sustainable territorial development based on the exploitation of three basic aspects: the landscape as a resource, maintenance of diversified economic activities supported by endogenous resources and continue with its insertion in Central Asturias.